2019
DOI: 10.1038/s42003-018-0253-x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling in Drosophila melanogaster mediates Aβ toxicity

Abstract: Alzheimer’s disease (AD) and diabetes are clinically positively correlated. However, the connection between them is not clarified. Here, using Drosophila as a model system, we show that reducing insulin signaling can effectively suppress the toxicity from Aβ (Amyloid beta 42) expression. On the other hand, Aβ accumulation led to the elevation of fly insulin-like peptides (ILPs) and activation of insulin signaling in the brain. Mechanistically, these observations are attributed to a reciprocal competition betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Neuropeptides and insulin signaling have been implicated in multiple aspects of sex-specific behavior and physiology including mating and reproduction 23,24 , and, as our data indicate, brain-expressed Tud may partially contribute to these processes in Drosophila. Interestingly, a recent study also showed the upregulation of tobi in the fly heads in response to the accumulation of β-amyloid peptide (Aβ) in the Alzheimer's disease Drosophila model 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Neuropeptides and insulin signaling have been implicated in multiple aspects of sex-specific behavior and physiology including mating and reproduction 23,24 , and, as our data indicate, brain-expressed Tud may partially contribute to these processes in Drosophila. Interestingly, a recent study also showed the upregulation of tobi in the fly heads in response to the accumulation of β-amyloid peptide (Aβ) in the Alzheimer's disease Drosophila model 25 .…”
Section: Resultsmentioning
confidence: 99%
“…PPARγ is a transcription factor that is present in the BACE1 promoter and reduces BACE1 activity (Chen et al, 2012) and transcriptionally regulates the expression of IDE in primary neurons (Du et al, 2009). Some studies have also demonstrated that IDE could reduce Aβ toxicity and promote Aβ clearance (Huang et al, 2019) as well as reduce the level of IDE or genetic mutation of IDE-altered AD pathology (Cook et al, 2003;Prince et al, 2003). To elucidate the mechanism of BEOV in inhibiting Aβ production and promoting Aβ clearance in the brain of APPSwe/PS1dE9 mice, the expression levels of PPARγ and IDE were assessed by Western blot analyses.…”
Section: Beov Up-regulated the Expression Of Pparγ And Ide In The Ad mentioning
confidence: 99%
“…1 f). In addition, FOXO is a downstream component of insulin/IGF signaling pathway, which modulation may be associated with Aβ toxicity [ 33 ].…”
Section: Resultsmentioning
confidence: 99%